Systematic estimation of insertion dates of endogenous bornavirus-like elements in vesper bats - MUKAI, Yahiro; HORIE, Masayuki; TOMONAGA, Keizo (Journal of Veterinary Medical Science, 2018)
Endogenous bornavirus-like elements (EBLs) are sequences derived from bornaviruses (the family Bornaviridae) that are integrated into animal genomes. They are formed through germline insertions of segments of bornaviral transcripts into animal genomes. Because EBLs are molecular fossils of bornaviruses, they serve as precious sources of information to understand the evolutionary history of bornaviruses. Previous studies revealed the presence of many EBLs in bat genomes, especially in vesper bats, and suggested the long-term association between bats and bornaviruses. However, insertion dates of EBLs are largely unknown because of the limitations of available bat genome sequences in the public database. In this study, through a combination of database searches, PCR, and sequencing approaches, we systematically determined the gene orthologies of 13 lineages of EBLs in bats of the genus Myotis and Eptesicus and family Vespertilionidae. Using the above data, we estimated their insertion dates: the EBLs in vesper bats were inserted approximately 14.2 to 53 million years ago. These results suggest that vesper bats have been repeatedly infected by bornaviruses at different points in time during evolution. This study provides novel insights into the evolutionary history of bornaviruses and demonstrates the robustness of combining database searches, PCR, and sequencing approaches to estimate insertion dates of bornaviruses.